Synthesis of qualitative research on drug use in the European Union: report on an EMCDDA project. European Monitoring Centre for Drugs and Drug Addiction - Fountain, J; Griffiths, P (European addiction research, 1999)
This paper is a synthesis of the information in the report Inventory, Bibliography and Synthesis of Qualitative Research in the European Union which was co-ordinated for the European Monitoring Centre for Drugs and Drug Addiction, Lisbon, Portugal, by the National Addiction Centre, London, UK. It is based on the work of a network of qualitative researchers from the European Union. The report includes detailed information from each member state on current qualitative projects, relevant publications from the last 10 years and a directory of those researchers active in this area. The paper introduces the project, outlines its future direction and discusses what can be defined as 'qualitative research'. Historical developments and the role of qualitative methodology in relation to research into drug use are examined. A summary of the project's findings is presented, and the relevance of qualitative research for policy-making is discussed. Finally, the methodology used to collect data for the project is described.